An Exploration of Marketing’s Impacts on Influencing Consumer Behavior and Society - Chheda, Kajal (Journal of Informatics Education and Research, 2023)
Marketing is an old skill that has been performed in some way or another since the days of Adam and Eve. Marketing is pervasive in today's society; it pervades almost every activity we do and every aspect of our lives. Marketing is a process. Marketing actions and tactics result in the availability of goods that please consumers while also profiting the businesses that sell them. Your morning tea, newspaper, breakfast, the outfit you put on for the day, the vehicle you drive, the phone in your pocket, the quick lunch you have at the fast-food joint, the PC at your desk, your internet connection, your e-mail ID, almost everything you use and everything in your environment has been influenced by marketing. Marketing has left an impression on them all, which may be obvious or subtle depending on the product and context/experience. However, it is very much present. The majority of your everyday actions are influenced by marketing. Marketing is a pervasive force. The technology-based global competition environment that pushes businesses to constructive transformation in order to ensure customer satisfaction has further increased the importance of marketing capabilities in business strategies. A significant number of studies conducted in different countries have shown that marketing spending is an investment that creates value for the company and has a positive impact on firm profitability, firm value or firm sales. This study contributes to the literature by summarizing the research findings on the effects of marketing investments on business performance. The relationship between market share and profitability has been widely discussed. Our findings suggest that businesses with relatively large market shares tend to have above-average rates of investment turnover, particularly working capital. Also, the ratio of marketing expense to sales is generally lower for high-share businesses than for those with small market shares. These differences are indications of economies of scale that may go along with strong market positions.
ISME
Keywords: Marketing; Strategy; organizational and performance